2012
DOI: 10.5539/ells.v2n1p21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Authentic Versus Non-authentic Aural Materials on EFL Learners’ Listening Comprehension

Abstract: The question put forward in this study was to pinpoint the impact of the authentic versus non-authentic listening materials on the listening comprehension of Iranian EFL subjects. After random selection, 80 upper-intermediate students from among all language institutes in Khoramshahr and Abadan cities, in Khuzestan province, Iran, took part in this study. The participants participated in two experimental treatment groups. During one semester, they were instructed in listening to authentic radio-tapes and non-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
2
18
1
Order By: Relevance
“…Potosi et al believed that when learners were exposed to video programs, not only did their comprehension improve but also they noticed the features of the English language such as stress, intonation, and pronunciation. Mousavi and Iravani (2012) investigated the impact of authentic versus non-authentic video materials on listening comprehension among Iranian EFL learners. In their study, they observed that authentic video materials had significant effects on gaining higher scores in both listening comprehension and proficiency test.…”
Section: Studies On Using Video Materials In Language Classesmentioning
confidence: 99%
“…Potosi et al believed that when learners were exposed to video programs, not only did their comprehension improve but also they noticed the features of the English language such as stress, intonation, and pronunciation. Mousavi and Iravani (2012) investigated the impact of authentic versus non-authentic video materials on listening comprehension among Iranian EFL learners. In their study, they observed that authentic video materials had significant effects on gaining higher scores in both listening comprehension and proficiency test.…”
Section: Studies On Using Video Materials In Language Classesmentioning
confidence: 99%
“…Based on beliefs of program efficacy, the subjects reported overall positive attitudes, and efficacy beliefs were, in turn, based on the metric of NS, authentic input as the standard. In research reports (Major, Fitzmaurice, Bunta, & Balasubramanian, 2002;Mousavi & Iravani, 2012), monographs of listening pedagogy (Flowerdew & Miller, 2005), and even classic teacher references (Nunan, 2003;Omaggio-Hadley, 1993), the advantages of NS authentic material is expounded and considerations for utilizing authentic listening in the classroom are posited. It is reasonable to conclude that to research L2 listening beliefs, a number of indicators should be designed to detect learners' beliefs on the role of NS, authentic input.…”
Section: Authentic Listening Beliefsmentioning
confidence: 99%
“…Pedagogically, the concept of authenticity is defined as "being as close a match as possible between the language and social context of the input which learners receive in the classroom and the language and social context of everyday life" (MacDonald, Badger, & White, 2000:253-254). The authentic video has been used in different ways for learners to enhance their listening comprehension skill (Canning-Wilson, 2000;Cakir, 2006;Erfani, Iranmehr & Davari, 2011;Mousavi & Iravani, 2012;Ismaili, 2013) but in this research, the researcher will try to investigate its effectiveness in writing skill. In selecting spoken text in the video, Widodo (2015:68-69) consider some criteria include connectivity, selectivity, authenticity, representativeness, neutrality, familiarity and intelligibility, and comprehensibility.…”
Section: Authentic Videomentioning
confidence: 99%
“…In addition, Corbally (2005: 376) also assumes that the use of a medium such as a video has the potential to be an interesting resource for students. The authentic video has been used in different ways for learners to enhance their listening comprehension skill (Canning-Wilson, 2000;Cakir, 2006;Erfani, Iranmehr & Davari, 2011;Mousavi & Iravani, 2012;Ismaili, 2013) but in this research, the researcher tried to investigate its effectiveness in writing skill. The researcher were more confidently choose the authentic video because Duffy (2008:124) argues that video as powerful educational and motivational tool, and as effective instructional video, it is not television-tostudent instruction but rather teacher-to-student instruction where it as a vehicle for discovery.…”
Section: Introductionmentioning
confidence: 99%